Liver X Receptor (LXR) Regulates Human Adipocyte Lipolysis - Stenson, Britta M. (American Society for Biochemistry and Molecular Biology, 2011)
The Liver X receptor (LXR) is an important regulator of carbohydrate and lipid metabolism in humans and mice. We have recently shown that activation of LXR regulates cellular fuel utilization in adipocytes. In contrast, the role of LXR in human adipocyte lipolysis, the major function of human white fat cells, is not clear. In the present study, we stimulated in vitro differentiated human and murine adipocytes with the LXR agonist GW3965 and observed an increase in basal lipolysis. Microarray analysis of human adipocyte mRNA following LXR activation revealed an altered gene expression of several lipolysis-regulating proteins, which was also confirmed by quantitative real-time PCR. We show that expression and intracellular localization of perilipin1 (PLIN1) and hormone-sensitive lipase (HSL) are affected by GW3965. Although LXR activation does not influence phosphorylation status of HSL, HSL activity is required for the lipolytic effect of GW3965. This effect is abolished by PLIN1 knockdown. In addition, we demonstrate that upon activation, LXR binds to the proximal regions of the PLIN1 and HSL promoters. By selective knock-down of either LXR isoform, we show that LXRα is the major isoform mediating the lipolysis-related effects of LXR. In conclusion, the present study demonstrates that activation of LXRα up-regulates basal human adipocyte lipolysis. This is at least partially mediated through LXR binding to the PLIN1 promoter and down-regulation of PLIN1 expression.